A unique profilin-actin interface is important for malaria parasite motility - Moreau, Catherine; Bhargav, Saligram P.; Kumar, Hirdesh; Quadt, Katharina; Strauss, Léanne; Kehrer, Jessica; Streichfuss, Martin; Spatz, Joachim P.; Wade, Rebecca C.; Frischknecht, Friedrich (PLoS pathogens, 2017)
Profilin is an actin monomer binding protein that provides ATP-actin for incorporation into actin filaments. In contrast to higher eukaryotic cells with their large filamentous actin structures, apicomplexan parasites typically contain only short and highly dynamic microfilaments. In apicomplexans, profilin appears to be the main monomer-sequestering protein. Compared to classical profilins, apicomplexan profilins contain an additional arm-like β-hairpin motif, which we show here to be critically involved in actin binding. Through comparative analysis using two profilin mutants, we reveal this motif to be implicated in gliding motility of Plasmodium berghei sporozoites, the rapidly migrating forms of a rodent malaria parasite transmitted by mosquitoes. Force measurements on migrating sporozoites and molecular dynamics simulations indicate that the interaction between actin and profilin fine-tunes gliding motility. Our data suggest that evolutionary pressure to achieve efficient high-speed gliding has resulted in a unique profilin-actin interface in these parasites.